PENGANGKATAN ANAK DALAM KAJIAN PERSPEKTIF HUKUM ISLAM - L. Tobing, R. Sondang (Faculty of Law, University of Palembang, 2021)
Adopted children in Islam are not biological children, thus prohibiting adoption with an intention to make other people's children become their own and equate in their heart's belief that the adopted child is their biological child. In Islam the basis of goodness; deeds and their damage is intention. That the intention of adopting a child is to worship in the framework of love as a fellow creature of God so that the child is not neglected in his life. The emotional closeness that exists because of the parenting factor does not cause an adopted child to be believed like he is a real biological child. However, in his upbringing, he is still obliged to treat him fairly and properly within the framework of loving him as a fellow creature. Adoption of children in Islam is child care carried out by adoptive parents (foster parents).